Nordic digital identification (eID) - Hansteen, Kjell (TemaNord, 2016)
This publication presents the survey results and policy recommendations of a Nordic study of national eID-systems. The countries that have been studied are Denmark, Finland, Iceland, Norway and Sweden. The aim of the study is to facilitate and lay a foundation for discussions about the similarities and differences in legal, organisational, technical and data approaches taken by the different countries. The survey data has been gathered with the assistance of the members of a project reference group. The data has been analysed and structured into a number of highlighted issues (chapter 1). The highlighted issues have been in turn used as baseline for a set of recommendations (chapter 9). The Nordic Council of Ministers has provided funding and facilitated the staffing of the reference group. The Norwegian Agency for Public Management and e-Government, Difi, has been the project owner and provided project resources.